2014
DOI: 10.2196/jmir.2945
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Messaging Preferences to Inform Development of Mobile Goal-Directed Behavioral Interventions

Abstract: BackgroundMobile messaging interventions have been shown to improve outcomes across a number of mental health and health-related conditions, but there are still significant gaps in our knowledge of how to construct and deliver the most effective brief messaging interventions. Little is known about the ways in which subtle linguistic variations in message content can affect user receptivity and preferences.ObjectiveThe aim of this study was to determine whether any global messaging preferences existed for diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
65
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 38 publications
8
65
0
Order By: Relevance
“…Results of our study are similar to other studies conducted in younger adolescents and older adults that have shown feasibility and acceptability of text messaging (Muench, Van Stolk-Cooke, Morganstern, Kuerbis, & Markle, 2014) to promote weight loss and/or PA (Gerber et al, 2009; Woolford, Clark, Strecher, & Resnicow, 2010; Woolford et al, 2011). In a study by Woolford and colleagues, young adolescent perspectives on the content of text messages in weight loss promotion were explored.…”
Section: Discussionsupporting
confidence: 88%
“…Results of our study are similar to other studies conducted in younger adolescents and older adults that have shown feasibility and acceptability of text messaging (Muench, Van Stolk-Cooke, Morganstern, Kuerbis, & Markle, 2014) to promote weight loss and/or PA (Gerber et al, 2009; Woolford, Clark, Strecher, & Resnicow, 2010; Woolford et al, 2011). In a study by Woolford and colleagues, young adolescent perspectives on the content of text messages in weight loss promotion were explored.…”
Section: Discussionsupporting
confidence: 88%
“…(34) Prior literature(12, 35) and our own formative work(9, 10) emphasize the importance of a positive tone and of participant-relevant language in automated interventions. Accordingly, all aspects of iDOVE’s content and structure were iteratively refined prior to this pilot to reflect participants’ own experiences, literacy levels, and definitions of “positive” language, using a human-centric, qualitative approach.…”
Section: Discussionmentioning
confidence: 96%
“…Similar to our findings, users preferred messages that highlighted the positive over the negative, were nonaggressive, and benefit-oriented messages. In addition, aspects such as correct spelling and grammar, directive rather than passive approach, and messages without “textese” (eg, abbreviations) were found to be more preferred [31]. …”
Section: Discussionmentioning
confidence: 99%